Keefektifan Konseling Kelompok Motivational Interviewing Untuk Meningkatkan Motivasi Belajar Peserta Didik: The Effectiveness of Motivational Interviewing Group Counseling to Increase Students' Learning Motivation - Dyah Indah Fatikasari; Denok Setiawati; Indah Ayu Mardiningsih (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2025)
This study explores the effectiveness of integrating Motivational Interviewing (MI) in group counseling to increase learners' motivation to learn. Motivational Interviewing, which focuses on exploring intrinsic motivation and addressing ambivalence, is applied in the context of group counseling to provide social and emotional support. The research method used library research with descriptive analysis to review literature related to MI and group counseling. The results showed that the combination of MI and group counseling significantly increased students' academic motivation, a change of 57.55% in the implementation of pre-action in cycles I and II. With positive impacts seen in increased engagement and academic achievement. This combined strategy helped students explore personal goals and overcome barriers to learning, as well as strengthening peer support. This research suggests the widespread application of MI-based group counseling methods at various levels of education as an effective strategy to support student motivation and learning outcomes, and makes an important contribution to the development of better educational interventions.